Analysis of relationship between optical properties of minerals and portland cement whiteness - Дорогань, Наталия Александровна; Черняк, Лев Павлович (Eastern-European Journal of Enterprise Technologies, 2015)
The relationship of mineralogical composition and optical properties of rock-forming minerals in the raw mix to the characteristics and phase composition of Portland cement clinker for gray and white cement production was investigated. The dependence of the clinker whiteness on the phase composition and optical properties of individual crystalline phases was considered. The influence of ferrohydroxides in the feedstock on the formation of C4AF type iron-containing crystalline phases, characterized by optical anisotropy, increased density indexes and refractive index (Ng=3,77) in gray cement clinker (20-25% whiteness) was confirmed. The formation of crystalline phases of the C12A7(Ng=2,85-2,90) mayenite type, relating to optically isotropic and transparent, with a relatively lower refractive index, as a factor of increasing the clinker whiteness (70-73%) in the firing of raw mixes based on the oxide system CaO – Al2O3 – SiO2 was shown. An example of obtaining high-whiteness clinker (80-83%) under the C12A7 synthesis intensification was given.